Glucagon-like peptide 1 and glucose-dependent insulinotropic peptide hormones and novel receptor agonists protect synapses in Alzheimer’s and Parkinson’s diseases - Hölscher, Christian (Frontiers in Synaptic Neuroscience, 2022)
Glucagon-like peptide 1 (GLP-1) and glucose-dependent insulinotropic peptide (GIP) are peptide hormones and growth factors. A major pathological feature of both Alzheimer dis-ease (AD) and Parkinson disease (PD) is the loss of synaptic transmission in the cortex in AD and the loss of dopaminergic synapses in the nigra-striatal dopaminergic projection. Several studies demonstrate that GLP-1 and GIP receptor agonists protect synapses and synaptic transmission from the toxic events that underlie AD and PD. In a range of AD animal models, treatment with GLP-1, GIP or dual GLP-1/GIP receptor agonists effectively protected cognition, synaptic trans-mission, long-term potentiation (LTP), and prevented the loss of synapses and neurons. In PD models, dopaminergic production resumed and synapses become functional again. Importantly, the GLP-1 receptor agonists exendin-4 and liraglutide have shown good protective effects in clinical trials in AD and PD patients. Studies show that growth factors and peptide drugs that can cross the blood-brain barrier (BBB) better are more potent than those that do not cross the BBB. We therefore developed dual GLP-1/GIP receptor agonists that can cross the BBB at an enhanced rate and that showed superior protective properties on synapses in animal models of AD and PD.